Perceived stress in Italian coaches and the effect of rebooting in sport activities - Santi Giampaolo; Costa Sergio; Montesano Cristina; Carraro Attilio; Bertollo Maurizio; di Fronso Selenia (Psihologija, 2024)
Perceived stress in Italian coaches and sport mental health were investigated during the rebooting of sport activities following the first COVID-19 lockdown period. A sample of 237 coaches from various sports were asked to answer the Italian version of the Perceived Stress Scale and the Sport Mental Health Continuum, together with reporting of demographic information. Coaches’ perceived stress levels were compared with data collected during the lockdown period. Women showed a significant decrease in their perceived stress levels compared to the lockdown period, whereas this was not true for men. Hierarchical regression indicated that, during the rebooting phase, increased age of coaches and their psychological well-being experienced in sporting contexts (a sport mental health dimension) were predictive of decreased perceived stress levels. Practical implications for practitioners working in this field are discussed in the conclusions.